Community Practitioners in Criminal Courts: Risk Logics and Multiply-Disadvantaged Individuals - Quirouette, Marianne (Theoretical criminology, 2018)
The role community practitioners play in lower criminal courts has traditionally been overlooked in the socio-legal literature. In this article, I analyse how they use discretion and contribute to courts' knowledge about and understanding of the problems clients (the accused) face. I focus on how they manoeuvre the courts, offering supports, service or housing; ‘vouching' for or documenting progress, good character, compliance and potential; or educating judicial actors about social context, or therapeutic perspectives around mental health, substance use or trauma. I advance understandings of how non-justice actors interpret and use risk logics, while contributing medical, cultural and sociological knowledge that can improve practices in lower criminal courts, particularly by destabilizing assumptions about criminogenic risk management, poverty and choice.